2023
DOI: 10.1097/mej.0000000000001042
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor and procalcitonin for risk stratification in patients with a suspected infection in the emergency department: a prospective cohort study

Abstract: van Gorp d,e and Yuri van der Does a Background and importance Early identification of patients at risk of clinical deterioration may improve prognosis of infected patients in the emergency department (ED). Combining clinical scoring systems with biomarkers may result in a more accurate prediction of mortality than a clinical scoring system or biomarker alone.Objective The objective of this study is to investigate the performance of the combination of National Early Warning Score-2 (NEWS2) and quick Sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It is also an anti-inflammatory agent involved in the regulation of cytokines. 24 Some studies 25 have indicated that PCT is significantly better than C-reactive protein and other inflammatory markers for determining the presence and severity of infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an anti-inflammatory agent involved in the regulation of cytokines. 24 Some studies 25 have indicated that PCT is significantly better than C-reactive protein and other inflammatory markers for determining the presence and severity of infection.…”
Section: Discussionmentioning
confidence: 99%